(untitled) (Iraqi Journal of Medical Sciences, 2024)
Background: Helicobacter pylori (H. pylori), is a Gram-negative bacterium that colonizes the human stomach. Persistence of H. pylori infection may lead to various gastrointestinal pathologies such as gastric cancer. Objective: To investigate the correlation between H. pylori antigen in stool and antibody with serum interleukin (IL)-6 and tumor necrosis factor-alpha (TNF-?). Methods: The participants were assigned into patients and controls, for both groups, rapid urease test, H. pylori stool antigen test, Anti-H. pylori IgA, and IgG, serum Il-6, and serum TNF-? were measured. Results: The mean serum levels of the IgA, IgG, IL-6, and TNF-? for the patients were as follows: 32.56±0.51 U/ml, 18.37±0.39 U/ml, 71.05±1.09 pg/ml, 54.72±1.01 pg/ml, respectively, while those of the controls were: 7.97±0.35 U/ml, 2.09±0.21 U/ml, 11.69±0.50 pg/ml, 3.76±0.23 pg/ml, respectively. The comparisons of all four markers showed very highly statistically significant difference between patients and controls (P